2020
DOI: 10.3390/ijms21113801
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Gene Correction to Understand ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease caused by the death of motor neurons in the spinal cord and brainstem. ALS has a diverse genetic origin; at least 20 genes have been shown to be related to ALS. Most familial and sporadic cases of ALS are caused by variants of the SOD1, C9orf72, FUS, and TARDBP genes. Genome editing using clustered regularly interspaced short palindromic repeats/CRISPR-associated system 9 (CRISPR/Cas9) can provide insights into the underlying genetics and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 85 publications
0
29
0
Order By: Relevance
“…42 Furthermore, targeting of ESS-B led to generation of the synonymous A36G mutation, which ameliorated the cellular phenotype of SMA iPSC-derived motor neurons. 42 Genome editing strategies for ALS HDR-based genome editing approaches have been used to correct a variety of SOD1 mutations in iPSCs from individuals with ALS (reviewed in Yun and Ha 43 ), demonstrating rescue of the ALS cellular phenotype in motor neurons derived from gene-corrected iPSCs (Figure 1D). Similar approaches have been exploited in iPSCs from people with mutations in FUS and TARDBP.…”
Section: Genome Editing Strategies For Smamentioning
confidence: 99%
“…42 Furthermore, targeting of ESS-B led to generation of the synonymous A36G mutation, which ameliorated the cellular phenotype of SMA iPSC-derived motor neurons. 42 Genome editing strategies for ALS HDR-based genome editing approaches have been used to correct a variety of SOD1 mutations in iPSCs from individuals with ALS (reviewed in Yun and Ha 43 ), demonstrating rescue of the ALS cellular phenotype in motor neurons derived from gene-corrected iPSCs (Figure 1D). Similar approaches have been exploited in iPSCs from people with mutations in FUS and TARDBP.…”
Section: Genome Editing Strategies For Smamentioning
confidence: 99%
“…Clustered regularly interspaced short palindromic repeats/CRISPR-associated system 9 (CRISPR/Cas9) genome editing: CRISPR/Cas9 can delete a copy of Ku80 (DNA repair protein) in C9orf72 iPSCs, leading to the decrease in Ku80 expression and pro-apoptotic protein levels. Thus, CRISPR/Cas9 approach can be used for C9orf72 repeat expansion to verify the pathological phenotype in patient-derived iPSCs and to determine gene-based therapies [182]. Studies have shown that once SOD1 gene is deleted, adeno-associated virus 9-Staphylococcus aureus Cas9-single guide RNA5 (AAV9-SaCas9-sgRNA5) will increase survival of SOD1 G93A mice by 54.6%, and significantly improve the performance of ALS transgenic mice.…”
Section: Gene Therapiesmentioning
confidence: 99%
“…With the application of CRISPR/Cas9 technology, isogenic iPSCs can be generated, allowing to exclusively focus on the specific disease-causing mutation [56], and to demonstrate a rescue of the disease-related cellular endophenotype. Isogenic iPSCs obtained by mutation correction in genes have been generated to rescue the ALS phenotype [57]. In another study, mutated dystrophin was successfully corrected in an iPSC model of Duchenne muscular dystrophy [58].…”
Section: Gene Editing-crispr-cas9 Technologymentioning
confidence: 99%